CONTENT OF HEAVY METALS (Cr, Cu, Pb, and Zn) IN MACROZOOBENTHOS AT JAKARTA BAY - Noverita Dian Takarina; Andrio Adiwibowo (JOURNAL OF COASTAL DEVELOPMENT, 2010)
Trace metal contamination of marine environments can be determined by measuring trace metalconcentration in sediments, water or biota. Biomonitor organisms have the advantages over othermeasurements that they concentrate the portion of metals that are in a biologically available form, and thisportion which is usually of interest when assessments is being made of trace metal contamination.Correspondingly, whole tissue trace metal concentrations of 4 metals in common Jakarta Bay benthic species(polychaetes, molluscs, crustaceans) from contaminated locations were measured. The mean concentrationfor Cu was 17.5 ± 21.8 μg g-1 dw in polychaetes, 11.9 ± 8.8 μg g-1 dw in molluscs, and 12.2 ± 5.5 μg g-1 dw incrustaceans. The mean concentration for Cr was 172.8 ± 262.5 μg g-1 dw in polychaetes, 31.8 ± 62.8 μg g-1dw in molluscs, and 28.5 ± 29.0 μg g-1 dw in crustaceans. The mean concentration for Zn was 152.4 ± 76.4μg g-1 dw in polychaetes, 132.0 ± 106.3 μg g-1 dw in molluscs, and 515.8 ± 503.5 μg g-1 dw in crustaceans.The mean concentration for Pb was 6.3 ± 13.6 μg g-1 dw in polychaetes and was 2.0 ± 4.5 μg g-1 dw inmolluscs. The study provides significant contribution to confirm the content of heavy metal in each commonbenthic species inhabits coastal Jakarta Bay.